The Effect of Dissemination of Resources and Information Approach on Energy and Fiber Intake in Overweight Students - Hadi, Anto Jamma; Yetti R, Erni; Manggabarani, Saskiyanto (Study Program of Nutrition, Public Health Faculty, Institut Kesehatan Helvetia, 2021)
Background; The incidence of overnutrition for elementary school children continues to increase rapidly throughout the world and has reached an alarming stage due to excessive energy intake. Students who are overweight are caused by the school environment selling a lot of foods containing saturated fat and low fiber which has an impact on increasing the amount of excessive energy in the body. Objectives; This study aims to assess the effect of the dissemination of resources and information approach on the nutritional intake of overweight students. Material and Method; This research was conducted in elementary schools in Makassar city with a quasi-experimental design conducted on overweight children in elementary school grades 4-5 consisting of 40 intervention groups and 40 control groups and purposive sampling. A 3-month research intervention with nutrition educators accompanied by the provision of modules and leaflets Data collection was carried out using pre-test and post-test as well as data processing and analysis using the SPSS program with chi-square test, Wilcoxon and Mann Whitney. Results; The results showed that both the intervention and control groups had a significant effect on energy intake and fiber intake during pre, post 1 and post 2 (p = 0.000 0.05). Conclusion;The conclusion is that there is an effect of the dissemination of resources and information approach on the nutritional intake of overweight students. Overweight students can manage their diet in a planned manner and increase fiber consumption and be active in physical activities.